Utilization of Statistics to Improve the Effectiveness of Guidance and Counseling Services in Schools - Halimahtun Syaddiyah; Daharnis; Rezki Hariko (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to examine the use of statistics in the evaluation of Guidance and Counseling (BK) services based on literature analysis. The evaluation of guidance and counseling services requires a systematic and data-based approach to ensure the effectiveness of the services provided to students. The results show that descriptive statistics are widely used to present basic data on services, while inferential statistics such as t-test, ANOVA, and regression are utilized to assess the effectiveness of interventions and relationships between variables. Outcome based evaluation is becoming an increasingly adopted approach to improving service quality. The main challenges identified were the limited competence of counselors in statistical analysis and the lack of systemic support in educational institutions. On the other hand, advances in technology and statistical software have made it easier to conduct quantitative service evaluations. This study emphasizes the importance of improving statistical literacy for counselors and the integration of data-based evaluation systems in the development of adaptive and effective counseling programs.